Investigating the fermentability of synthetic medium-density fiberboard wastewater to alcohol and effects of cofermenting the wastewater with sucrose. Issue 2 (17th February 2020) - Rashama, Charles; Matambo, Tonderayi
ABSTRACT: The impact of cofermentation on ethanolic fermentation performance of medium-density fiberboard wastewater (MDFW) was investigated. Sugar concentration in MDFW was adjusted by cofermentation of the MDFW with sucrose. Separate shake flask fermentation experiments were conducted on a dilute synthetic MDFW (with and without inhibitors) and a sucrose–MDFW blend as substrates. Instant dry baker's yeast ( Saccharomyces cerevisiae ) was used as the biocatalyst. Fermentation performance was measured by calculation of the fermentation efficiency of each experiment. The calculation was based on fermentable sugars only, and excluded pentoses which are not fermented by ordinary yeast. The study revealed that direct fermentation of dilute MDFW at around 80–100 g/L sugar concentration was less efficient (64.02%) than fermentation of MDFW solutions of 130–160 g/L sugar concentration which recorded fermentation efficiencies way above 75%. The authors conclude that MDFW is fermentable to alcohol using Saccharomyces cerevisiae, and that cofermenting MDFW with sucrose possibly obtained from other waste streams like sugar molasses enhances the fermentability.